ผลกระทบของนโยบายประชานิยมภายใต้รัฐบาล พ.ต.ท. ทักษิณ ชินวัตร ที่มีต่อเครือข่ายหนี้สินชาวนาแห่งประเทศไทย - พุฒ พงศ์รพีพร (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objective of this thesis is to explore Thaksin Shinawatra government s populist policies with respect to their meaning, their characteristics, and their implications. The study also examines the effects of populist policies on the Peasant Debt Network of Thailand (PDNT) and its response to those policies. The study finds that Thaksin s Populist Policies have an official objective to solve the poverty problem of grassroots people. However, in reality, it is found that many grassroots problems cannot be solved through the government populist policies. One major obstacle is the government s hidden and primary motive to garner its popularity, rather than actually solving the grassroots problems. The populist policies have affected the PDNT which already has its own policy named "Farmers Restoration and Development Fund (FRDF). Like the populist policies, the FUND is geared toward solving the problems of grassroots people. The populist policies have mechanisms that restrain the movement according to FRDF s principles. They also thwart the expansion of PDNT s membership. But in response, PDNT attempted at first to take part in the populist policies, yet discovering that those policies cannot solve the problems of PDNT s members. The policies negatively affected the existing unity of the grassroots, while depending their implementation on some of the existing governmental organization, such as the Department of Provincial Administration, which already have not received much credit on solving many problems at the grassroots level. Therefore, PDNT terminated its involvement with the policies, while criticizing and opposing the populist policies. In the end, PDNT s movement is mainly in accordance with FRDF s principles.